Tindak Pidana Korporasi Bagi Perusahaan Yang Terlibat Dalam Pencucian Uang Hasil Penjualan Narkotika - Wibowo, Aris; Eddy, Triono; Sahari, Alpi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The National Agency was formed to further intensify the eradication of narcotics crime is one of the extra ordinary crimes. It turns out that narcotics crime also provides a fact that to track the proceeds of the sale of narcotics, the money is diverted, on behalf of, or formed by another corporation as a camouflage so that it is not tracked by the police. Initially, corporations cannot be convicted for various reasons, but later corporations can be convicted. This study aims to analyze the criminal policy of corporate criminal acts for companies involved in money laundering from the sale of narcotics as well as obstacles and solutions carried out by BNN of North Sumatra province in the handling of corporate criminal cases for companies involved in money laundering from narcotics sales. The results of this study indicate the criminal policy of corporate criminal acts for companies involved in money laundering from the sale of narcotics with the existence of money laundering laws that were not previously explicitly regulated, including that the subject of criminal acts for corporations for companies. The obstacle faced by the North Sumatra National Narcotics Agency is the difficulty of obtaining information related to searches regarding objects resulting from money laundering crimes. Another obstacle is the confiscation of the assets of the suspect who must cooperate with the bank, the lack of facilities and infrastructure and the low professionalism of law enforcement.